The Effect of Eucalyptus Oil Steam Inhalation on Respiratory Rate in Toddlers with Acute Respiratory Infection (ARI) - Astriyani Astriyani; Ika Permanasari; Destria Efliani; Tengku Isni Yuli Lestari Putri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Acute Respiratory Infection (ARI) is one of the major health issues contributing to high mortality rates among toddlers, both globally and in developing countries. This study aims to identify the effectiveness of eucalyptus oil steam inhalation therapy in regulating the respiratory rate of toddlers suffering from ARI in the working area of Meskom Public Health Center.This research employs a case study method with a descriptive design. The study population consists of 147 toddlers, with a sample of 16 toddlers diagnosed with ARI in the Meskom Public Health Center's working area. The research was conducted in December. The study results indicate that before administering eucalyptus oil steam inhalation therapy, toddlers' respiratory rates ranged from 30 to 47 breaths per minute, with a median of 41.94 breaths per minute. After the therapy, the respiratory rate changed, ranging from 28 to 46 breaths per minute, while the median remained at 41.94 breaths per minute. Based on these findings, it is recommended that the Meskom Public Health Center consider utilizing eucalyptus oil steam inhalation as an additional method in managing ARI in toddlers.